2018
DOI: 10.1590/1413-81232018233.09082016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de anemia e correlação da concentração de hemoglobina com fatores cognitivos em idosos

Abstract: Prevalência de anemia e correlação da concentração de hemoglobina com fatores cognitivos em idososPrevalence of anemia and correlation between the concentration of hemoglobin and cognitive factors among the elderly 44;35;85),14;03;01), estado nutricional (β = 0,16; IC95%: 0,01;0,06), comprometimento de memória (β = 0,12;06;01),13;06;01 nutritional status (β = 0.16; 95% CI: 0.01, 0.06), memory impairment (β = 0.12;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
(62 reference statements)
3
6
0
2
Order By: Relevance
“…The present study found prevalence of anaemia of 12.2% in the elderly studied. These findings are in line with other brazilian studies that involved elderly people enrolled in the FHU, developed by Buffon et al (2015), Barbosa et al (2006) and Sousa et al (2018), who reported rates between 8, 8% and 12.5%. Moreover, when com-pared to the 10.6% prevalence of anaemia founded by Le (2016) in the developed non-institutionalized civilian population of the United States, the value observed in most of the brazilian studies cited remains higher, which is reaffirmed by the fact that the US study only analyzes individuals over 65 years old, which would tend to raise the prevalence found.…”
Section: Discussionsupporting
confidence: 92%
“…The present study found prevalence of anaemia of 12.2% in the elderly studied. These findings are in line with other brazilian studies that involved elderly people enrolled in the FHU, developed by Buffon et al (2015), Barbosa et al (2006) and Sousa et al (2018), who reported rates between 8, 8% and 12.5%. Moreover, when com-pared to the 10.6% prevalence of anaemia founded by Le (2016) in the developed non-institutionalized civilian population of the United States, the value observed in most of the brazilian studies cited remains higher, which is reaffirmed by the fact that the US study only analyzes individuals over 65 years old, which would tend to raise the prevalence found.…”
Section: Discussionsupporting
confidence: 92%
“…The same pattern was observed in an American study 24 . Brazilian investigations with the elderly also found higher prevalence of anemia in the males compared to the femals 8,9,14 . The effect that men are more likely to have anemia in older age groups may be related to the reduction in testosterone production, which has a significant impact on lowering hemoglobin levels in the body 28 .…”
Section: Discussionmentioning
confidence: 83%
“…Among the elderly population using the Unified Health System (SUS) in Campina Grande, the prevalence was 12.5%. % in 2010 14 . In the elderly in long-term care facilities, the prevalence of anemia reached 38.0% in Salvador 15 .…”
Section: Palavras-chavementioning
confidence: 99%
“…The level of hemoglobin in the serum was significantly correlated with cognitive impairment. Additionally, studies have demonstrated that EPO can have neuroprotective effects ( Fan et al, 2012 ), the production of EPO can be stimulated by anemic hypoxia in the brain, and anemia is an independent risk factor of cognitive decline ( Sousa et al, 2018 ).…”
Section: The Potential Biomarkers Related To Ckdmentioning
confidence: 99%